2015
DOI: 10.3390/su7079395
|View full text |Cite
|
Sign up to set email alerts
|

Financial Development, Environmental Quality and Economic Growth

Abstract: Abstract:In this study, the relationships between financial development, environmental quality and economic growth are studied based on data from 102 countries over the period 1980-2010 using the generalized method of moments (GMM) estimation. The econometric results show the following three basic conclusions: First, both financial development and environmental quality have a significant impact on economic growth and should be included in the production function of the economic growth model as important variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…The findings showed that financial development increases the emissions of CO2. These studies include (Boutabba, 2014;Jamel & Maktouf, 2017;Li, Zhang, & Ma, 2015;Ozturk & Acaravci, 2013;Saboori, Sulaiman, & Mohd, 2012;Zhang, 2011), while some studies found a negative relationship between financial development and CO2 emissions. These studies include (Mulali, Tang, & Oztur, 2015;Saidi & Mbarek, 2017;Xing, Jiang, & Ma, 2017).…”
Section: B the Relationship Between Remittances And Co2 Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings showed that financial development increases the emissions of CO2. These studies include (Boutabba, 2014;Jamel & Maktouf, 2017;Li, Zhang, & Ma, 2015;Ozturk & Acaravci, 2013;Saboori, Sulaiman, & Mohd, 2012;Zhang, 2011), while some studies found a negative relationship between financial development and CO2 emissions. These studies include (Mulali, Tang, & Oztur, 2015;Saidi & Mbarek, 2017;Xing, Jiang, & Ma, 2017).…”
Section: B the Relationship Between Remittances And Co2 Emissionsmentioning
confidence: 99%
“…During the last few years, many researchers have conducted surveys on the issue of "Impact of Financial Development on Carbon Emission." For instance, (Ayeche, Barhoumi, & Amin, 2016;Başarir & Çakir, 2015;Farhani & Ozturk, 2015;Li, Zhang, & Ma, 2015;Mugableh, 2015) concluded that financial development increases the level of carbon emissions. Two main factors can elaborate on the impact of financial development on environmental degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Following previous studies, SO 2 and TSP emission intensity, SO 2 and TSP emissions per capita, and SO 2 and TSP emissions per unit area were calculated to measure air pollution [ 44 47 ]. Pollution intensity refers to the indicator of pollution emissions per industrial gross domestic product (GDP) (industrial economic output).…”
Section: Methodsmentioning
confidence: 99%
“…The sustainable lifestyle is subordinated to the living conditions, which is why the ecological economy is promoted, which comes as a result of implementing the economic sustainability. An ecological economy requires the creation of renewable resources and permanent monitoring of the emissions that cause a negative environmental impact [7]. The results of the economic entity are according to the economic sustainability, closely related to the environment and social sustainability [1].…”
Section: Introductionmentioning
confidence: 99%